Money-related meanings and practices in low-income and poor families - Daly, M (SAGE Publications, 2015)
This article focuses on the meanings and repertoires of action associated with money in low-income and poverty circumstances. Based on interviews with 51 people, the analysis reveals how people on a low income actively engage with money as a way of situating themselves in their complex worlds. Money is investigated at two levels: praxis and orientation regarding spending, and as part of self-identity. In regard to spending, people displayed two main repertoires: one was functional (viewing money as a way of meeting material need) and the second relational (with money interpreted in regard to relationships and upholding of personal and familial values). These repertoires in turn link into self-understanding and world view. For people in poverty and low income, money can be a disabler, detracting from a valued identity and sense of future but a counter, more positive, orientation normalises lack of money, by reference to skills and character development and core values and relationships. The research as a whole underlines the complexity of money in low-income or poverty settings, the agency and creativity which people bring to its use and the diverse meanings they invest it with.